Long-term outcomes of laparoscopic sleeve gastrectomy vs. laparoscopic Roux-en-Y gastric bypass: Special focus on procedure selection, gastroesophageal reflux, and quality of life - Grönroos, Sofia (fi=Turun yliopisto|en=University of Turku|, 2023)
Background: Severe obesity is an increasing global epidemic. To date, metabolic bariatric surgery (MBS) is the only treatment for severe obesity with good and sustainable long-term weight loss and remission of obesity related comorbidities. The gold standard procedure is laparoscopic Roux-en-Y gastric bypass (LRYGB), but since 2014, laparoscopic sleeve gastrectomy (LSG) has been the most common MBS procedure in the world. This transition took place before any available longterm data for LSG. As obesity is a chronic disease, the long-term outcomes are of vital clinical importance in outcome assessment and procedure selection. Aims: The main purpose of this thesis was to assess long-term outcomes of MBS. The first and second study assessed the outcomes of the Sleeve vs. Bypass (SLEEVEPASS) randomized clinical equivalence trial at 7 and 10 years. Firstly, the aim was to compare both weight loss (percentage excess weight loss, %EWL) and quality of life (QOL) and their possible association after LSG vs. LRYGB at 7 years. The second predefined 10-year analysis assessed weight loss and remission of comorbidities, QOL, and overall morbidity and mortality. In addition, a special focus was added to evaluate both symptoms and endoscopic findings of gastroesophageal reflux and more specifically the prevalence of Barrett’s esophagus (BE). The third aim of this thesis was to assess the feasibility of Individualized Metabolic Surgery (IMS) score in facilitating procedure selection in patients with severe obesity and type 2 diabetes (T2DM) using a large merged individual patient 5-year data of the two largest RCTs comparing LSG and LRYGB (SLEEVEPASS and SM-BOSS). Results: The mean %EWL was 47% after LSG vs. 55% after LRYGB at 7 years, and 44% vs. 51% at 10 years, respectively. The two procedures were not equivalent, but the difference was not clinically relevant based on the predefined equivalence margins. There was no difference in long-term QOL or in the remission of T2DM, dyslipidemia, obstructive sleep apnea, or complication rate or BE prevalence between LSG and LRYGB at 10 years. Hypertension remission was superior after LRYGB. Esophagitis was more prevalent after LSG. In all IMS score severity stages, there was no difference between the procedures in T2DM remission rates. Conclusions: %EWL was greater after LRYGB, and the procedures were not equivalent for weight loss, but both resulted in good and sustainable weight loss at long-term. Long-term QOL and remission of comorbidities were similar between the procedures except for hypertension and esophagitis, where LRYGB had superior outcomes. IMS score did not facilitate procedure selection.

Mahalaukun kavennusleikkauksen vs. mahalaukun ohitusleikkauksen pitkäaikaistulokset Tausta: Vaikea lihavuus on maailmanlaajuinen epidemia. Lihavuuskirurgia on tutkitusti ainoa vaikean lihavuuden hoitomuoto, jolla pitkäaikaisseurannassa saavutetaan hyvä ja pysyvä painonlasku sekä liitännäissairauksien paraneminen. Laparoskooppinen Roux-en-Y mahalaukun ohitusleikkaus (LRYGB) on edelleen lihavuuskirurgian leikkausmenetelmien kultainen standardi, vaikka 2014 lähtien laparoskooppinen mahalaukun kavennusleikkaus (LSG) on ollut maailman eniten käytetty. Tämä muutos tapahtui ennen kuin LSG:n pitkäaikaistuloksia oli saatavilla. Vaikean lihavuuden ollessa krooninen sairaus pitkäaikaistulokset ovat kliinisesti olennaisia hoidon tulosten arvioinnissa ja leikkausmenetelmän valinnassa. Tavoitteet: Väitöskirjassa tutkitaan lihavuuskirurgian pitkäaikaistuloksia. Ensimmäinen ja toinen osatyö käsittelivät satunnaistetun Sleeve vs. Bypass (SLEEVEPASS) –tutkimuksen 7- ja 10-vuotistuloksia. 7v-seurannassa verrattiin painonlaskua (percentage excess weight loss, %EWL) ja elämänlaatua sekä niiden assosiaatiota. 10v-seurannassa arvioitiin painonlaskua, liitännäissairauksia, elämänlaatua ja komplikaatioita sekä refluksitaudin oireita ja endoskooppisia löydöksiä ja Barrettin ruokatorven (BE) esiintyvyyttä. Kolmanneksi tutkittiin Individualized Metabolic Surgery (IMS)-pisteytyksen käytettävyyttä leikkausmenetelmän valinnassa tyypin 2 diabeetikoilla (T2DM) käyttäen kahden satunnaistetun tutkimuksen 5-vuotisyhdistelmädataa (SLEEVEPASS ja SM-BOSS). Tulokset: %EWL 7 ja 10 vuoden kohdalla oli LSG:n jälkeen 47% ja 44% ja vastaavasti 55% ja 51% LRYGB:n jälkeen. Leikkaukset eivät olleet ekvivalentteja, mutta niiden ero ei ollut kliinisesti merkittävä etukäteen asetettujen ekvivalenssimarginaalien pohjalta. Elämänlaadussa ei ollut eroa. Liitännäissairauksien paranemisessa (T2DM, dyslipidemia, uniapnea), komplikaatioissa, tai BEn esintyvyydessä ei ollut eroa 10v-seurannassa. LSG:n jälkeen oli enemmän esofagiittia. Verenpainetaudin paraneminen oli tehokkaampaa LRYGB:n jälkeen. T2DM remissiossa ei ollut eroa toimenpiteiden välillä missään IMS-pisteytyksen T2DM-vaikeusasteissa. Johtopäätökset: LRYGB:n %EWL oli korkeampi, mutta ero ei ollut tutkimusasetelman pohjalta kliinisesti merkittävä, molemmissa leikkauksissa todettiin hyvä ja pysyvä painonlasku. Liitännäissairauksien paranemisessa, elämänlaadussa tai BEn esiintyvyydessä ei ollut eroa. Esofagiittia oli enemmän LSG:n jälkeen, LRYGB oli parempi verenpainetaudin hoidossa. IMS-pisteytys ei helpottanut leikkausmenetelmän valintaa.